On a simple technique to measure the airborne noise in a car interior using substitution source. (1st January 2012) - Putra, Azma; Munir, Fudhail A.; Juis, Clinton D.
From various methods of measuring noise in a motor vehicle, a technique to separate the airborne and structure-borne noise is of interest as an important measure to improve the noise control treatment. This paper proposes a simple technique to measure the contribution of the airborne noise in a vehicle cabin using substitution source method. A cone loudspeaker was used as the substitution source and the airborne transfer function was measured. The technique has successfully separated the airborne transmission with the intersection frequency at roughly 400 Hz with the structure-borne noise. It is found that this is independent of the engine speed.